2022
DOI: 10.33200/ijcer.605900
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships between Preschoolers’ Play Behaviors, Social Competence Behaviors and Their Parents’ Parental Attitudes

Abstract: This article may be used for research, teaching, and private study purposes. Any substantial or systematic reproduction, redistribution, reselling, loan, sub-licensing, systematic supply, or distribution in any form to anyone is expressly forbidden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The two versions of the Preschool Play Behavior Scale (PPBS) were also considerably used ( n total = 6), namely the Preschool Play Behavior Scale-Hong Kong (PPBS-HK) ( n = 1) (Leung, 2017), and the PPBS ( n = 5) (Aslan, 2020; Coplan & Rubin, 1998; Lagacé-Séguin & d’Entremont, 2006; Suhonen et al, 2015; Uygun & Kozikoğlu, 2019), which assess the risk of social isolation in ludic settings regarding non-social play, more specifically the components of reticent, solitary passive, solitary active, social and rough, and tumble behavior.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The two versions of the Preschool Play Behavior Scale (PPBS) were also considerably used ( n total = 6), namely the Preschool Play Behavior Scale-Hong Kong (PPBS-HK) ( n = 1) (Leung, 2017), and the PPBS ( n = 5) (Aslan, 2020; Coplan & Rubin, 1998; Lagacé-Séguin & d’Entremont, 2006; Suhonen et al, 2015; Uygun & Kozikoğlu, 2019), which assess the risk of social isolation in ludic settings regarding non-social play, more specifically the components of reticent, solitary passive, solitary active, social and rough, and tumble behavior.…”
Section: Resultsmentioning
confidence: 99%
“…From the studies analyzed, and shown in Table 1, it is possible to observe a prevalence of instruments applied directly to children ( n = 19) (Aslan, 2020; Barton, 2015; Coplan et al, 2001, 2014; Fallon & MacCobb, 2013; Fehr & Russ, 2013, 2014; Gal-Szabo et al, 2019; Lautamo et al, 2011; Lucisano et al, 2021; Marcelo & Yates, 2020; Minnett et al, 1994; Pierce-Jordan & Lifter, 2005; Saracho, 1995, 1996, 1999; Shim et al, 2001; Shire et al, 2018; So et al, 2020), followed by the application by teachers ( n = 9) (Bulotsky-Shearer et al, 2012; Coolahan et al, 2000; Coplan & Rubin, 1998; Ergin & Ergin, 2017; Fantuzzo et al, 1995; Lagacé-Séguin & d’Entremont, 2006; Leung, 2017; Suhonen et al., 2015; Uygun & Kozikoğlu, 2019) and by parents ( n = 4) (Gagnon et al, 2014; Karaca et al, 2020; LaForett & Mendez, 2017; Tröster & Brambring, 1994).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations